PENGARUH VARIASI ALAT BANTU TERHADAP MOTIVASI DAN KETERAMPILAN GERAK DASAR ROLL BELAKANG - Ikhwan Prayogi; Herman Tarigan; Frans Nurseto (JUPE (Jurnal Penjaskesrek), 2013)
This study aims to determine how large an increase in motivation and backward roll basic movement skills and motivation is there any relationship with increasing skill behind the roll after roll back treated using a variety of learning aids for 16 sessions. The method used is an experimental. The samples used were 40 students who were divided into two groups. Initial tests conducted on the first week of February 2013, and then continued with the treatment in the experimental group during the 6 weeks. This is indicated by an increase in the average value of the results from 60.1 to 70.5 versa student motivation can be improved with the use of varied tools, visible from the difference in the value of motivation in the experimental class and the control class where experimental class scored an average of 74 , 7 whereas 62.5 kotrol class with the conclusion that there is a significant effect using a variety of learning tools to roll back penigkatan basic skills, learning using a variety of tools can affect student motivation, and no significant association with an increased motivation to learn motor skills basic backward roll.Kata kunci : variasi, alat bantu, motivasi, roll belakang.